Determinants UiTM online waqf acceptance / Muhammad Farhan Abdul Rahaman - Abdul Rahaman, Muhammad Farhan (2017)
Waqf is defined as irrevocable property for the purpose use of benefits or usufruct to society that intend for religious or charitable purposes. Nowadays, waqf became one of Islamic product that faces revolution because of passage of time. In order to ease Muslim society to make contributions, waqf institutions accept monetary donations for waqf purposes that known as cash waqf. In the era of technology, cash waqf also can be made by using online platform that called online waqf. Educational institutions also use cash waqf in order to back up their financing for development. 120 questionnaires being distribute in UiTM campus Jengka in order to collect data that consists two sections: demographic and independent variables. Independent variables are perceived usefulness, perceived ease of use, perceived religiosity and amount of information which make effect to acceptance on UiTM online waqf dependant variable. The researcher used Statistical Package for Social Science (SPSS) to analyse the data from questionnaire that use validity, reliability, descriptive, correlation and regression analysis.